1979
DOI: 10.1083/jcb.83.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the participation of actin microfilaments and bristle coats in the internalization of gap junction membrane.

Abstract: Thin sections of rabbit granulosa, human SW-13 adrenal cortical adenocarcinoma, and mouse B-16 melanoma cells revealed an apparent single-layered basket of 4-to 7-nm filaments surrounding cytoplasmic gap junction vesicles . This interpretation was based upon apparent longitudinal, cross, and en face sections of structures surrounding the vesicle profiles in tissue treated with tannic acidglutaraldehyde . In granulosa cells incubated with the S-1 fragment of heavy meromyosin, arrowhead-decorated filaments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
2
4

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(88 citation statements)
references
References 40 publications
9
73
2
4
Order By: Relevance
“…3). Thin-section electron microscopy of rabbit granulosa, human SW-13 adrenal cortical adenocarcinoma, and mouse B-16 melanoma cells showed that cytoplasmic GJ vesicles are surrounded by actin-containing filaments [Larsen et al, 1979]. Consistent with these data were further electron microscopical studies characterizing the plasma membrane and its cytoskeletal undercoat at sites of GJ invagination.…”
Section: Gap Junction Removal and Degradationsupporting
confidence: 70%
“…3). Thin-section electron microscopy of rabbit granulosa, human SW-13 adrenal cortical adenocarcinoma, and mouse B-16 melanoma cells showed that cytoplasmic GJ vesicles are surrounded by actin-containing filaments [Larsen et al, 1979]. Consistent with these data were further electron microscopical studies characterizing the plasma membrane and its cytoskeletal undercoat at sites of GJ invagination.…”
Section: Gap Junction Removal and Degradationsupporting
confidence: 70%
“…Early ultrastructural analyses revealed large vesicular double-membrane GJ structures, AGJs, in the cytoplasm of cells derived from many different tissues (Ginzberg and Gilula, 1979;Larsen et al, 1979;Pfeifer, 1980;Leach and Oliphant, 1984;Mazet et al, 1985;Severs et al, 1989). Here, we demonstrate by expressing Cx43-GFP (a major GJ subunit protein) in HeLa cells, that entire GJ plaques can be internalized into one of the coupled cells to form these cytoplasmic, double-membrane GJ vesicles (Figure 1).…”
Section: Formation Of Double-membrane Gj Vesiclesmentioning
confidence: 99%
“…In an early ultrastructural study, clathrin had been speculated to be involved in GJ internalization (Larsen et al, 1979); however, a robust colocalization of clathrin with GJs, M. Piehl et al…”
Section: Proteins Involved In Gj Internalizationmentioning
confidence: 99%
See 2 more Smart Citations